Diagenetic Environment of Sandstones from the Ermaying Formation (Middle Triassic), North-eastern Margin of the Ordos Basin, China: Implications for the Erosion Vulnerability of the Pi Sandstone. (January 2019) - Liu, Li; Jiang, Yanan; Liu, Na; Yu, Lei; Bai, Hanggai; Jiang, Lingxu
Abstract: A hard layer of calcite cemented sandstones overlaid weakly consolidated mudstones occur in the Middle Triassic, Ermaying Formation in the eastern margin of the Ordos Basin, China, were examined to reveal the diagenetic environment of Pi sandstone. The Pi sandstone refers to a type of terrigenous clastic rock assemblage composed mainly of sandstone, siltstone and mudstone with red and white color, which is characterized by exposing or being covered with sand or loess, vulnerable to weathering and erosion, distributed in the contiguous area of Shaanxi province, Inner Mongolia autonomous region and Shanxi province in China, and formed during Late Paleozoic–Mesozoic. The "Pi" comes from the folk name (pishuang) of arsenic in Chinese, the appellation of the "Pi sandstone" means that it is harmful to soil and water conservation. The Pi sandstone samples were collected from a sheet-like sandstones deposited in ephemeral river. Petrographic observation show that the samples studied carry a semi-arid climate signal, are cemented by mictrie (microcrystalline calcite), sparry (coarse-crystalline) calcite as well as quartz overgrowths. The δ 13 C and δ 18 O values of calcite in the studied are –6.2 to – 3.8 ‰ PDB and from–10.2 to –8.9‰ PDB, respectively. The evidence from petrography and stable isotopes suggests that the cementation of the sandstone mainly occurred in the vadose - phreatic environment.